KEPEMILIKAN PROPERTI BAGI WARGA NEGARA ASING YANG BERKEDUDUKAN DI INDONESIA - Khasanah, Dian Dewi (PROGRESIF: Jurnal Hukum, 2022)
In principle, only Indonesian citizens can own land in Indonesia. With the government's program to improve development and the Indonesian economy by promoting investment by bringing in foreign investors, the government issued a policy to regulate property ownership for foreign citizens who wish to own a residence in Indonesia. Property that can be owned by foreign nationals can only be owned with the status of Right to Use and Right to Rent for a certain period of time. The purpose of this limitation of the period of property ownership for foreign nationals is to protect land owned by Indonesian citizens from various exploitation and covert foreign domination. Ownership of property by foreign nationals is regulated in various laws and regulations and their implementing regulations. With the issuance of these various regulations, it is hoped that there will be harmonization between property ownership arrangements for foreign citizens and residential ownership for Indonesian citizens.